2015
DOI: 10.1073/pnas.1505231112
|View full text |Cite
|
Sign up to set email alerts
|

Role of a ribosomal RNA phosphate oxygen during the EF-G–triggered GTP hydrolysis

Abstract: Elongation factor-catalyzed GTP hydrolysis is a key reaction during the ribosomal elongation cycle. Recent crystal structures of G proteins, such as elongation factor G (EF-G) bound to the ribosome, as well as many biochemical studies, provide evidence that the direct interaction of translational GTPases (trGTPases) with the sarcin-ricin loop (SRL) of ribosomal RNA (rRNA) is pivotal for hydrolysis. However, the precise mechanism remains elusive and is intensively debated. Based on the close proximity of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…In particular, the interaction of the phosphate group of A2662 with the side chain of His84 is likely responsible for the stabilization of the rotated conformation of His84 towards the nucleotide in the activated state . This is in agreement with the results of atomic mutagenesis studies, where replacement of one of the two nonbridging phosphate oxygens of A2662 with a methyl group resulted in a complete loss of GTPase stimulation of EF‐G by the ribosome . Also Asp21 might take part in the stabilization of the TS by SRL, which would explain why this residue is present in trGTPases, but not in Ras‐like GTPases.…”
Section: The Ribosome As a Gapsupporting
confidence: 85%
See 1 more Smart Citation
“…In particular, the interaction of the phosphate group of A2662 with the side chain of His84 is likely responsible for the stabilization of the rotated conformation of His84 towards the nucleotide in the activated state . This is in agreement with the results of atomic mutagenesis studies, where replacement of one of the two nonbridging phosphate oxygens of A2662 with a methyl group resulted in a complete loss of GTPase stimulation of EF‐G by the ribosome . Also Asp21 might take part in the stabilization of the TS by SRL, which would explain why this residue is present in trGTPases, but not in Ras‐like GTPases.…”
Section: The Ribosome As a Gapsupporting
confidence: 85%
“…20 This is in agreement with the results of atomic mutagenesis studies, where replacement of one of the two nonbridging phosphate oxygens of A2662 with a methyl group resulted in a complete loss of GTPase stimulation of EF-G by the ribosome. 95 Also Asp21 might take part in the stabilization of the TS by SRL, 58 which would explain why this residue is present in trGTPases, but not in Ras-like GTPases. Recent high-resolution structures of the ribosome-bound EF-G show the side chain of the respective Asp residue coordinating a Mg 21 ion close to the crucial A2662, indicating that the GTPase-activated state might also involve a rearrangement of Asp21.…”
Section: The Ribosome As a Gapmentioning
confidence: 99%
“…Structural studies have revealed that nucleotide A2662 of the SRL places the catalytic His-84 residue in EF-Tu and His-87 in EF-G into their activated positions (16,17,29). Recently, a more detailed role for A2662 was revealed by the atomic mutagenesis approach; namely, that the non-bridging phosphate oxygen of A2662 participates in the activation of GTP hydrolysis on trGTPases (30). Here, A2662 in the SRL is shown to interact with the catalytic His-86 residue to place it into its activated position, further corroborating a universal mechanism of trGTPase activation through the SRL.…”
Section: Structure Of the Ribosome-ef4-gdpcp Complexmentioning
confidence: 99%
“…Ribosome‐dependent GTPases bind to the prokaryotic 70S ribosome complex through both the sarcin‐ricin loop (SRL) and the GTPase‐associated center (GAC) . Recent structural and mechanistic data support a model of GTPase activation, whereby a phosphate oxygen from A2662 in the SRL is a strong determinant for GTP hydrolysis . By contrast, the role of the GAC is less understood with several ambiguous findings.…”
Section: Introductionmentioning
confidence: 99%